Site-specific growth of MOF-on-MOF heterostructures with controllable nano-architectures: beyond the combination of MOF analogues. Issue 14 (16th March 2020) - Liu, Chao; Lin, Lina; Sun, Qiang; Wang, Jing; Huang, Rong; Chen, Wenyi; Li, Shumin; Wan, Jingjing; Zou, Jin; Yu, Chengzhong
Abstract : A site-specific epitaxial-growth strategy is developed to synthesize two types of MOF-on-MOF heterostructures with elaborately designed architectures, which are comprised of two MOFs with totally different compositions. Abstract : The integration of different metal–organic frameworks (MOFs) into one system has led to the recent combinatorial innovation of various MOF-on-MOF hybrids; however control over their site-specific growth beyond MOF analogues remains challenging. In this work, a site-specific epitaxial-growth strategy is developed to synthesize MOF-on-MOF heterostructures comprised of two MOFs with totally different compositions. A guest MOF (ZIF-8) is epitaxially grown on the specific {110} facets of a host MOF (MIL-125). Moreover, the position of ZIF-8 growth on MIL-125 is also selectable by using MIL-125 hosts with {110} facets exposed on either the corner or side surface. Consequently, two MIL-125@ZIF-8 heterostructures with elaborately designed different architectures are synthesized. Benefiting from the high adsorption capacity of ZIF-8 and the photocatalytic activity of MIL-125, the MIL-125@ZIF-8 heterostructures demonstrate synergistically enhanced photocatalytic performance compared to single MOF subunits. Moreover, the corner growth leads to higher activity than the side growth of the MIL-125@ZIF-8 heterostructures. Our contribution paves the way for the rational design of composite MOFs with tunable compositions and nanostructures using the crystal engineering approach.